Anteseden Kolaborasi Rantai Pasok Pada Toko Laptop - Zainuddin Latuconsina; Retno S Susilawati; Pandu Cakranegara; Uli Wildan Nuryanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to analyze the influence of dependence, coordination, trust, and commitment to supply chain collaboration. This study used Partial Least Square (PLS) analysis tools. Using data from a sample of 33 laptop stores in Ambon City. The results showed that dependence does not affect supply chain collaboration, coordination has a positive effect on supply chain collaboration, trust has a positive effect on supply chain collaboration, commitment has a negative effect on supply chain collaboration, and commitment has a negative effect on supply chain collaboration.